Portugal: The Three Lost Empires - (:unkn) unknown (My University, 2012)
René Pélissier’s article is a major contribution to understand the elaboration of the Portugese colonization as a sui generis model. He explains how the third and last empire, known as the luso African one, which mainly encloses Angola and Mozambique, was build up until the final collapsing in 1975. It also describes in a very accurate manner the cultural and historical basis of this Empire by evocating the shape of the two former Portugese Empires and how they impact on the next and last one.
Keywords: African Research